(untitled) (Islamic Sciences Journal, 2023)
ABSTRACT The study reveals the function of the current presumption in highlighting the meaning and its influence on the choice of Korani Quranic readings as a crucial component of contextual relationships linking the article to the location where speech arises, as well as the goals and trade secrets of these readings in linguistic levels and grammatical issues. As a result, the research was divided into a prelude to the context of the situation in the language and three investigators: Initial examination: Using the acoustic and pure levels of the current assumption and merging two requirements: Current presumption by tide to indicate maximization is the first requirement. The second requirement is current presumption in terms of verb. The third requirement is current presumption at the grammar level in three claims. The first requirement is current presumption in pronouns. The second requirement is current presumption in subordinates. The third requirement is current presumption in terms of name. The most notable findings on which it stood were stated since the present presupposition was questioned.